(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
The goal of pharmaceutical care is to maximize therapeutic results and reduce any sort of medical errors by fostering interprofessional collaboration. Nurses play a very important role in medication safety and providing the best pharmaceutical care to patients because they are often the frontliners in the healthcare system. They help the patient adhere to their dosage regimen and usually are the first ones who report any signs of adverse drug responses. Moreover, using digital healthcare tools, such as electronic medication administration records (eMAR) or telemedicine can ease inter-professional collaboration. This review analyzed case studies and literature focusing on digital health tools, the WHO guidelines, and European Council recommendations to explore the possibilities of nursedriven pharmaceutical care. Major aspects, such as interprofessional collaboration, evidence-based practices, and advanced technologies, such as artificial intelligence and wearables were considered for their impact on patient care. Interprofessional collaboration improved patients’ compliance, reduced prescribing errors, and enhanced treatment outcomes. However, some relevant barriers were identified: deficient training, power imbalances, and communication failures. Some promising digital technologies include AI, wearables, and data analytics applied to address these issues to hasten the delivery of care. Medicine can be enhanced by removing obstacles to cooperation through mutual respect, training, and the incorporation of cutting-edge technologies. The use of digital tools and evidencebased procedures enables nurses to monitor and customize patient care better. Issues such as hierarchical dynamics and lack of interprofessional education need to be addressed to encourage productive teamwork and enhance patient outcomes. The inter-personnel collaboration has resulted in better therapeutic responses in patients and it has been reported to reduce medication errors and thereby improve patient adherence and therapeutic results. Nurses are better equipped to monitor and customize care because of advanced technologies, such as wearables and data analytics. Safe and efficient medication management requires nurse-driven pharmaceutical care backed by interprofessional teamwork and Evidence-Based Practice. Furthermore, investing in digital technologies and cooperative training will aid in smooth collaboration and optimized pharmaceutical care.